Advancing male age differentially alters levels and localization patterns of PLCzeta in sperm and testes from different mouse strains - Kashir, J; Mistry, BV; Gumssani, MA; Rajab, M; Abu-Dawas, R; AlMohanna, F; Nomikos, M; Jones, C; Abu-Dawud, R; Al-Yacoub, N; Coward, K; Lai, FA; et al. (Asian Society of Andrology, 2020)
Sperm-specific phospholipase C zeta (PLCζ) initiates intracellular calcium (Ca2+) transients which drive a series of concurrent events collectively termed oocyte activation. Numerous investigations have linked abrogation and absence/reduction of PLCζ with forms of male infertility in humans where oocyte activation fails. However, very few studies have examined potential relationships between PLCζ and advancing male age, both of which are increasingly considered to be major effectors of male fertility. Initial efforts in humans may be hindered by inherent PLCζ variability within the human population, alongside a lack of sufficient controllable repeats. Herein, utilizing immunoblotting, immunofluorescence, and quantitative reverse transcription PCR (qRT-PCR) we examined for the first time PLCζ protein levels and localization patterns in sperm, and PLCζ mRNA levels within testes, from mice at 8 weeks, 12 weeks, 24 weeks, and 36 weeks of age, from two separate strains of mice, C57BL/6 (B6; inbred) and CD1 (outbred). Collectively, advancing male age generally diminished levels and variability of PLCζ protein and mRNA in sperm and testes, respectively, when both strains were examined. Furthermore, advancing male age altered the predominant pattern of PLCζ localization in mouse sperm, with younger mice exhibiting predominantly post-acrosomal, and older mice exhibiting both post-acrosomal and acrosomal populations of PLCζ. However, the specific pattern of such decline in levels of protein and mRNA was strain-specific. Collectively, our results demonstrate a negative relationship between advancing male age and PLCζ levels and localization patterns, indicating that aging male mice from different strains may serve as useful models to investigate PLCζ in cases of male infertility and subfertility in humans.